VD_FINDINFO Décision / 2011 / 594 vom 26. August 2011 - VD Tribunal cantonal (2011)
DIFFAMATION, MENACEDROIT PÉNAL, CLASSEMENT DE LA PROCÉDURE | 173 CP, 180 CP, 310 CPP (CH), 393 al. 1 let. a CPP (CH), 393 CPP (CH)